Imagem corporal, aspectos nutricionais e atividade física em estudantes - Rossi, Daniela Sastre (2014)
One of the most difficult tasks in adolescence is the acceptance of modified body due to puberty events. Dissatisfaction with body image can lead to the practice of restricted diet and exercise in excess, and bring risks of poor nutrition, depression and eating disorders. The school is a privileged place to influence and guide students, and should reflect and work with relevant issues for their health. The aim of this study was to assess the body image satisfaction and its relationship with nutritional status, physical activity level, dietary habits and nutritional knowledge of 175 students from 5th to 8th grade at a public school in Santa Maria, RS, Brazil, considering the interventions on issues related to health promotion on such variables. Questionnaires were applied concerning body image satisfaction, nutrition knowledge, dietary habits and physical activity of students. Measures of body weight and height were used to calculate the nutritional status. The first test was conducted in April, and the second test in December, both in 2011. Pearson chi-square test and Spearman correlation test were applied. The significance level was 5%. The students were 50.9% male and 49.1% female. In males, there was no significant correlation between body image satisfaction and any variables in the first test, but in the second test, it was correlated with nutritional status (r=0.592, p<0.01). In the first test for females, body image was correlated with nutritional status (r=0.301, p<0.01) and nutritional knowledge (r=0.290, p<0.01); in the second test it maintained its correlation with nutritional status (r=376, p<0.01) and nutritional knowledge (r=0.257, p=0.024) and also with physical activity level (r=0,251, p= 0,036).The results indicate that, in both sexes, as it increases the nutritional status, increases the level of dissatisfaction with body image. Especially girls, when dissatisfied with their body image, have a higher level of nutritional knowledge and when satisfied, routinely engage in more physical activity. We observed it s important to detect students concerns about relevant aspects of their growth and development in order to plan educational activities to allow they can adopt healthy behaviors in their current and future life.